Міжнародна правотворчість як категорія - Чаплюк, О.І. (Часопис Київського університету права, 2009)
Статья анализирует взгляды философов, ученых-юристов относительно понятия и сущности международного правотворчества. На основании такого исследования автор дает свое определение понятия международного правотворчества, выделяет и раскрывает основные признаки этой деятельности. Ключевые слова: правотворчество, международное правотворчество, субъекты международного правотворчества, международные организации. The article gives the analysis of philosopher’s and jurist’s opinion шn the concept and essence of international lawmaking process. On the basis of such research the author gives his own definition of the concept of international lawmaking process distinguish and reveal its main features. Key words: law making process, international lawmaking process, participants of international lawmaking process, international organizations.